Density functional response approach for electric properties of molecules - Pal, Sourav; Sophy, K. B. (International Conference on Computational Methods in Sciences and Engineering (ICCMSE 2005), 2005)
We review in this paper an implementation of the response approach to the Kohn-Sham (KS) density functional theory (DFT) for obtaining the linear and non-linear electric response properties of molecules using Gaussian type orbital basis centered on atoms. We have made a formulation in which the response of the electron density through the solution of the coupled perturbed Kohn-Sham (CPKS) equations has to be obtained only once, instead of iteratively as in the case of completely analytic procedure. Our method is based on a numerical finite-field solution of derivative KS operator, followed by analytic solution of CPKS equation. Further, using the response of the electron density, the dipole moment, polarizability and first-hyperpolarizability of the molecules are evaluated. The method is particularly useful for large systems. We tested our method using HF, BH, H2O and CO as test molecules, for which, high quality ab initio results are available. Further, our study of possible incorporation of non-dynamical electron correlation by studying BH and HF at several internuclear distances is discussed.
International Conference on Computational Methods in Sciences and Engineering (ICCMSE 2005), Corinth, GREECE, OCT 21-26, 2005
Keywords: Density functional theory; molecular properties; polarizability; Response approach

Density functional static dipole polarizability and first-hyperpolarizability calculations of Na-n (n=2, 4, 6, 8) clusters using an approximate CPKS method and its comparison with MP2 calculations - Sophy, K. B.; Calaminici, Patrizia; Pal, Sourav (Journal of Chemical Theory and Computation, 2007)
{We report the static dipole polarizability and first-hyperpolarizability of the sodium atom clusters, Na-n

Deprotonation of 1,2-dialkylpyridinium ions: a DFT study of reactivity and site selectivity - Gupta, Neelima; Garg, Reena; Shah, Kirti Kr.; Tanwar, Akhilesh; Pal, Sourav (Journal of Physical Chemistry A, 2007)
A site-selectivity model, based on the Fukui function as a local reactivity descriptor, has been applied to 1.2-disubstituted pyridinium ions incorporating two competing sites of similar reactivity, i.e., 1-methylene and 2-methylene, which may undergo deprotonation depending on the nature of substituent present on these moieties. Applicability of the local HSAB rule, in context with the Li-Evans' generalized HSAB principle suggesting the hard-hard interactions to be controlled by minimum Fukui function, has been illustrated. Global and local reactivity descriptors have been computed by carrying out DFT calculations at B3LYP/6-31++G** level using Mulliken and NPA methods for charge analysis. A comparison with the calculated deprotonation energies involving two sites indicates that the observed site selectivity in differently substituted pyridinium ions is better explained by the Li-Evans rule of minimum Fukui function for hard-hard interactions.

Dipole moments and polarizabilities of some small radicals using constrained variational response to fock-space multi-reference coupled-cluster theory - Manohar, Prashant Uday; Pal, Sourav (Chemical Physics Letters, 2007)
In this Letter, we present dipole moments and polarizabilities of some open-shell doublet radicals, obtained analytically using constrained variational response to Fock-space (FS) multi-reference (MR) coupled cluster (CC) theory. These radicals can be treated as electron attached (EA) states of the corresponding closed-shell cations. Additionally, we also report analytical polarizabilities of some doublet radicals, which can be considered as ionized (IP) states of the corresponding anions. We compare our results with finite field FSMRCC response and the available benchmark results. (c) 2007 Elsevier B.V. All rights reserved.

Density functional investigations of electronics structure and dehydrogenation reactions of Al- and Si-substituted magnesium hydride - Kelkar, Tuhina; Pal, Sourav; Kanhere, Dilip G. (ChemPhysChem, 2008)
{The effect on the hydrogen storage attributes of magnesium hydride (MgH2) of the substitution of Mg by varying fractions of Al and Si is investigated by an ab initio plane-wave pseuodopotential method based on density functional theory. Three supercells, namely, 2 x 2 x x 3 x 1 x 1 and 5 x 1 x 1 are used for generating configurations with varying amounts (fractions x=0.0625, 0.1, and 0.167) of impurities. The analyses of band structure and density of states (DOS) show that, when a Mg atom is replaced by Al, the band gap vanishes as the extra electron occupies the conduction band minimum. In the case of Si-substitution, additional states are generated within the band gap of pure MgH2-significontly reducing the gap in the process. The reduced band gaps cause the Mg-H bond to become more susceptible to dissociation. For all the fractions, the calculated reaction energies for the stepwise removal of H-2 molecules from Al- and Si-substituted MgH2 ore much lower than for H-2 removal from pure MgH2. The reduced stability is also reflected in the comparatively smaller heats of formation (Delta H-f) of the substituted MgH2 systems. Si causes greater destabilization of MgH2 than Al for each x. For fractions x = 0.167 of Al
Keywords: band structure; Density functional calculations; hydrides; Hydrogen storage; Thermodynamics

Density functional investigation of relativistic effects on the structure and reactivity of tetrahedral gold clusters - De, Himadri Sekhar; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2009)
The influence of relativistic effects on the structure, vibrational modes, and reactivity of recently discovered tertrahedral gold clusters (Au(19) and Au(20)) are investigated using density functional methods. The intramolecular reactivity of the clusters was analyzed using density functional-based reactivity descriptors. The work shows that whereas the structural properties and vibrational modes are considerably affected by the relativistic effects, the reactivity trends based on Fukui function calculation on various atoms within this cluster remain unaffected by the absence or presence of relativistic effects. The reactivity descriptors reveal that the vertex atoms are the most reactive ones in Au(20) toward a nucleophilic attack. On the other hand, atoms connecting the missing vertex edge with the pyramid base along with the vertex atom are the most reactive for a nucleophilic attack in Au(19). The atoms lying at the center of each face are favorable for an electrophilic attack in both cases. Interestingly, the atoms with a missing cap in Aulg are highly favorable for electrophilic attack, and Au(20) has more sites for a favorable nucleophilic attack.

Descriptors as probes for inter-molecular interactions and external perturbation - Pal, Sourav (Applications of Density Functional Theory to Chemical Reactivity, 2012)
In this article, different reactivity descriptors have been reviewed. Conceptual density functional theory is an important area where a lot of interesting developments in terms of descriptors and molecule interactions have taken place in recent years. This review will highlight our own work on such development of descriptors and their applications to characterise stability and reactivity in molecule systems.
Keywords: Conceptual density functional theory; Electric field effect; Global reactivity descriptors; HSAB; Local HSAB; Local reactivity descriptors

Dinitrogen activation by silicon and phosphorus doped aluminum clusters - Das, Susanta; Pal, Sourav; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2014)
N-2 reduction is crucial for life, and very few catalysts are currently available to carry out this process at ambient temperature and pressure. In the present work, density functional theory based calculations reveal doped aluminum clusters to be highly reactive toward molecular nitrogen and hence are prospective materials for its activation at low temperatures. Calculations on silicon and phosphorus doped aluminum clusters with 5-8 atoms demonstrate an enhanced N-2 activation with respect to their pristine ground state and high energy counterparts. This increased efficiency of N-2 activation by doped ground state Al clusters is corroborated by an increment of the N N bond length, a red shift in N N bond stretching frequency, and adsorption energy (E-ad). Ab initio molecular-dynamics simulations demonstrate consequential efficiency of doped clusters toward dinitrogen activation at finite temperature. The ability of doped clusters toward activation of molecular nitrogen is site and shape sensitive. In short, this theoretical study highlights the critical role of doping foreign impurities for future endeavors in the design of cost-effective and efficient catalysts for N-2 activation at ambient temperatures. This observation may spur further studies in the field of aluminum nanocatalysis by doping silicon and phosphorus atom in aluminum clusters.

Dissociative adsorption of molecular hydrogen on BN-doped graphene-supported aluminum clusters - Kumar, Deepak; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2017)
The present work demonstrates dissociative adsorption of molecular hydrogen on supported and unsupported aluminum Wclusters (Al-n, n = 4-8, 13) using density functional theory based calculations. The studies reveal that the presence of a BN-doped graphene surface support reduces the dissociative adsorption barrier of the bond in molecular hydrogen on even atom clusters. In particular, supported Al-6 demonstrates a barrier-less dissociative adsorption toward the H-2 molecule. These results demonstrate the excellent potential of supported Al nanoparticles for hydrogen storage and also the potential of doped graphene systems are catalyzing supports.

Dissociative chemisorption of hydrogen molecules on defective graphene-supported aluminium clusters: a computational study - Kumar, Deepak; Govindaraja, Thillai; Krishnamurty, Sailaja; Kaliaperumal, Selvaraj; Pal, Sourav (Physical Chemistry Chemical Physics, 2018)
Using periodic density functional theory-based calculations, in the present study, we address the chemical bonding between aluminium clusters (Al-n, n = 4-8 and 13) and monovacant defective graphene. The adsorption strength of the above-mentioned aluminium clusters is fivefold (approximate to 3 to 5 eV) higher on defective graphene as compared to the earlier reported values on non-defective graphene and BN-doped graphene. The Bader charge analysis and different charge densities reveal that this adsorption is driven by significant charge transfer from the Al clusters to defective graphene. Thus, chemisorbed Al clusters demonstrate high activity towards dissociative adsorption of molecular hydrogen.